The Use of San in the Lugano Alphabet. A Survey of Cisalpine Celtic Onomastics - Blanca María Prósper (Вопросы ономастики, 2023)
The so-called “Lugano alphabet” is a northern Italian script that derives from the Etruscan alphabet. It was used to write Celtic texts belonging to the Lepontic language, uncovered in the centre of the Gallia Transpadana (Lombardy in Italy and Ticino in southern Switzerland), ranging from the 6th c. to the 1st c. BC, and a later variety called Cisalpine Gaulish, again located in the Transpadana (Lombardy and Piedmont in Italy), whose earliest texts date from the 4th c. BC, and which represents a later wave of immigrants or invaders. This dialect is distinguished from the former by a few morphological traits, like the patronymic suffix -ikno vs. Lepontic -alo-. While the Lugano script is deciphered in its entirety, some pending issues remain as to the actual use of some of its letters, its evolution and possible external influence from related alphabets. This work will address the problem of the so-called “butterfly sign,” a letter transliterated as <ś>, which shows different shapes, some of them easily confusable with <m>, and goes back to Greek san. For the “butterfly sign” a high number of synchronic values and etymological origins has been proposed. The article attempts to show that its use overlaps with that of zeta, transliterated as <z>. Both may have had a single value, and the reflected phoneme is in both cases a voiceless affricate that goes back to Indo-European /st/, /ts/ or /ds/, to epenthesis of /t/ in a sequence *-ns#, or to affrication of /d/ in coda position. The author also evaluates the possibility that the occurrence of san and tau gallicum in some contexts, specifically in codas, is due to mere phonemic reallocation not mediated by sound change.